Mechatronic development of an in-pipe microrobot with intelligent active force control - Sabzehmeidani, Yaser (2012)
In this research, the development of an in-pipe microrobot system with intelligent active force control (AFC) capability was investigated and presented, including both simulation and experimental studies. Three actuated microrobot mechanisms driven by pneumatic, piezoelectric and voice-coil actuators were modelled and simulated in a constrained environment inside a pipe. The mechanisms were then embedded into the proposed AFC-based control strategy. The worm-like movement of these microrobots with the respective actuators were effectively modelled using the impact drive mechanism (IDM). A classic proportional-integralderivative (PID) controller was first designed and applied to the microrobot system to follow a desired trajectory in the presence of disturbances, which may be created due to the frictional force or fluid viscosity inside a pipe. Later, an AFC-based controller was utilized to enhance the system dynamic performance by robustly rejecting the disturbances. To estimate the inertial mass of the AFC loop, artificial intelligence (AI) techniques, namely the variants of fuzzy logic (FL) and iterative learning algorithms (ILA) were explicitly employed. The dynamic response of the fully developed model of the in-pipe microrobot systems (with three different actuators) subject to various input excitations and disturbances was rigorously explored and numerically experimented. This involved the parametric study and sensitivity analysis to observe and to analyse the effects of a number of influential parameters that were deemed to have positive impact on the system performance. The simulation work was validated through an experimental investigation performed on a rig prototype that employed the voice-coil actuated mechanism to drive the selected AFC-based microrobot scheme, considering the given operating and loading conditions. Full mechatronic approach was adopted in the design of the rig by integrating the related sensors, actuator, mechanical parts and digital controller in a hardware-in-the-loop simulation (HILS) configuration. Parametric study was carried out to complement the simulation counterpart by taking into account the different settings and working environments. From the experimental results, the developed inpipe microrobot system was proven to be effective and robust in its trajectory tracking, in spite of the existence of various excitation inputs and external disturbances. This implied that the produced experimental responses were in good agreement with those acquired via simulation. The outcomes of the study shall provide a strong foundation for furthering the design of specific in-pipe microrobot applications, such as visual inspection of the inner surface of pipes, fault-diagnostics, obstacle removal and other related tasks.